Source apportionment of polycyclic aromatic hydrocarbons in road dust in Tokyo - Pengchai P. (2014)
This study was aimed at investigating source apportionment of PAHs in urban road dust. Seven kinds of PAHs sources were defined: diesel vehicle exhaust, gasoline vehicle exhaust, tire, asphalt-pavement, asphalt or bitumen, petroleum products excluding tire and asphalt, and the combustion products except for those in vehicle engines. Using cluster analysis combined with principal component analysis, 189 source data were classified into 11 source groups (S1-S11) based on the content percentage of 12 individual PAHs (12-PAH profiles). Thirty-seven dust samples on nine streets in Tokyo were collected and analyzed for 12-PAH profiles. In order to estimate the PAHs, contributions of S1-S11 to dust samples, the multiple regression analysis was performed. The 12-PAH profiles of each dust sample and those of 11 source groups were applied as dependent and independent variables, respectively. We defined the comparative contribution of each source group as the ratio of each regression coefficient to the sum of them. The result revealed that diesel vehicle exhaust, tire, and pavement were the major contributors of PAHs in the road dust.